2021
DOI: 10.1177/14604582211017944
|View full text |Cite
|
Sign up to set email alerts
|

How the Wakamola chatbot studied a university community’s lifestyle during the COVID-19 confinement

Abstract: This work aimed to study the effect of confinement on weight and lifestyle using the Wakamola chatbot to collect data from 739 adults divided into two groups (341 case-control, 398 confinement). Nutrition score (0–100 scale) improved for men (medians 81.77–82.29, p < 0.05), with no difference for women (medians 82.29 in both cases). Both genders reduced the consumption of sweetmeats and sugared drinks ( p < 0.01); men increased their consumption of vegetables, salad, and legumes ( p < 0.01). Both gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 50 publications
(129 reference statements)
0
13
0
1
Order By: Relevance
“…A summary and detailed description of the study characteristics are shown in Table 1 and Multimedia Appendix 3 [ 25 , 26 , 29 - 47 ] and Multimedia Appendix 4 [ 25 , 26 , 29 - 37 , 39 - 47 ]. The chatbot programs included Wakamola [ 30 - 32 ], WaznApp [ 33 ], WeightMentor [ 25 ], SWITCHes [ 34 ], MobileCoach [ 35 ], PathMate2 [ 36 ], and Lark Weight Loss Health Coach AI [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A summary and detailed description of the study characteristics are shown in Table 1 and Multimedia Appendix 3 [ 25 , 26 , 29 - 47 ] and Multimedia Appendix 4 [ 25 , 26 , 29 - 37 , 39 - 47 ]. The chatbot programs included Wakamola [ 30 - 32 ], WaznApp [ 33 ], WeightMentor [ 25 ], SWITCHes [ 34 ], MobileCoach [ 35 ], PathMate2 [ 36 ], and Lark Weight Loss Health Coach AI [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most (8/23, 35%) of the studies focused on promoting a healthy diet and exercise, whereas only 4% (1/23) studies focused on a healthy diet, exercise, and stress management ( Figure 2 and Multimedia Appendix 4 ). In all, 11 out of the 14 (79%) planned or trialed experimental studies [ 26 , 29 - 33 , 35 - 37 , 40 , 43 - 45 ] reported program durations that ranged from 1 hour to 12 months [ 30 - 32 ]. Only 1 study mentioned the intention of comparing algorithms to yield accurate behavioral predictions [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations